Phenolic Profile and Susceptibility to Fusarium Infection of Pigmented Maize Cultivars - Bernardi, Jamila; Stagnati, Lorenzo; Lucini, Luigi; Rocchetti, Gabriele; Lanubile, Alessandra; Cortellini, Carolina; De Poli, Giovanni; Busconi, Matteo; Marocco, Adriano (Frontiers in Plant Science, 2018)
Maize is a staple food source in the world, whose ancient varieties or landraces are receiving a growing attention. In this work, two Italian maize cultivars with pigmented kernels and one inbred line were investigated for untargeted phenolic profile, in vitro antioxidant capacity and resistance to Fusarium verticillioides infection. “Rostrato Rosso” was the richest in anthocyanins whilst phenolic acids were the second class in abundance, with comparable values detected between cultivars. Tyrosol equivalents were also the highest in “Rostrato Rosso” (822.4 mg kg-1). Coherently, “Rostrato Rosso” was highly resistant to fungal penetration and diffusion. These preliminary finding might help in breeding programs, aiming to develop maize lines being more resistant to infections and with improved nutraceutical value.